2009
DOI: 10.1097/iae.0b013e3181ac23da
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Functional Outcome After 23-Gauge Vitrectomy, Peeling, and Intravitreal Triamcinolone for Idiopathic Macular Epiretinal Membrane

Abstract: Twenty-three-gauge sutureless transconjunctival vitrectomy is a safe and effective technique for the treatment of idiopathic macular epiretinal membranes. The concomitant administration of intravitreal triamcinolone acetonide after pars plana vitrectomy may speed up and improve the anatomic and functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 48 publications
2
38
1
5
Order By: Relevance
“…A previous report on concomitant administration of intravitreal triamcinolon (IVTA) with macular surgery for ERM described the short-term visual recovery after use of IVTA. 24 It was noted that the level of achieved vision within 1 week is almost identical to the final VA data after 6 months. On the basis of these data, the authors suggest that the use of IVTA gives an important benefit by accelerating visual recovery.…”
mentioning
confidence: 53%
“…A previous report on concomitant administration of intravitreal triamcinolon (IVTA) with macular surgery for ERM described the short-term visual recovery after use of IVTA. 24 It was noted that the level of achieved vision within 1 week is almost identical to the final VA data after 6 months. On the basis of these data, the authors suggest that the use of IVTA gives an important benefit by accelerating visual recovery.…”
mentioning
confidence: 53%
“…However, other studies have shown quicker visual recovery and fewer complications with small-gauge trans-conjunctival sutureless vitrectomy techniques for ERM removal. [14][15][16] One of the limitations of this study was the use of VA as the sole measure of surgical success. Metamorphopsia is also a significant contributor to morbidity in patients with ERMs and it has been shown that, even though VA alone may not improve following ERM removal, metamorphopsia and quality of life does.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde 39 hastada 23-G TSV ile ERM soyulması ve intravitreal triamsinolon asetonid enjeksiyonu ile ortalama 7 aylık takip sonunda %74 olguda 3 sıra ve daha fazla görme artışı olduğu bildirilmiştir. 17 Bir başka çalış-mada, 23-G TSV kullanılarak İSY yardımıyla ERM soyulması gerçekleştirilmiş ve cerrahi sonrası 1. günde preoperatif görme keskinliği ile aynı seviyeye geldiği bildirilmiştir. 16 İSY kullanılarak 20-gauge (20-G) PPV ile makular epiretinal membran cerrahisi sonuçlarını bildiren bir çalışmada, ortalama 9,3 aylık takip sonunda %50 olguda 2 sıra ve üzerinde görme artışı elde edilmiştir.…”
Section: Gereç Ve Yöntemunclassified
“…[13][14][15] Çeşitli çalışmalarda, 23-G transkonjonktival sütürsüz vitrektomi (TSV) yöntemi ile ERM soyulmasının etkinliği ve güvenirliği bildirilmiştir. [16][17][18] Ancak literatürde, 23-G TSV ile TM ve BM'nin birlikte kullanıldığı çift boyama yöntemi ile ERM cerrahisi yapıldığını bildiren bir çalışma yoktur.…”
unclassified